Current approaches to managing fear of cancer recurrence; a descriptive survey of psychosocial and clinical health professionals. Issue 4 (1st November 2013) - Thewes, B.; Brebach, R.; Dzidowska, M.; Rhodes, P.; Sharpe, L.; Butow, P.
Abstract Objective Fear of cancer recurrence (FCR) is common amongst cancer survivors and help with this problem is the most frequently reported unmet need in this population. This study investigated how FCR is perceived and managed by clinical health professionals (medical and nursing staff) and psychosocial professionals in oncology settings. Methods Clinical health professionals and psychosocial professionals in oncology settings received emailed invitations from their professional organisation to participate in an online survey. Results Data from 77 clinical health professionals and 64 psychosocial professionals indicate that FCR is perceived as common and challenging to manage. Thirty‐one percent of psychosocial professionals estimated FCR is present in >50% of cancer survivors seen in their practise. Only a minority (21%) of clinical staff reported always referring patients with high levels of FCR to psychosocial support. Strategies for managing FCR differed considerably amongst psychosocial professionals, and most reported that aspects of acceptance and commitment therapy and/or cognitive behaviour therapy were helpful. Greater than 99% of participants were interested in training to help patients manage FCR. Conclusions Fear of cancer recurrence is commonly identified in oncology settings and a common focus of discussion in follow‐up care. However, patients with high levels of FCR are not routinely referred to psychosocial staff, and barriers to referral to psychosocial care should be investigated. The diversity of approaches reported by psychosocial professionals suggests lack of consensus regarding management of FCR, indicating that the development effective, theoretical‐based intervention and evidence‐based intervention for FCR is a matter of priority. Copyright © 2013 John Wiley & Sons, Ltd.